IMPLEMENTATION OF REGIONAL REGULATION (RR) NUMBER 11 OF 2013 REGARDING WASTE MANAGEMENT IN BATAM CITY - Kristina Dwi Putri; Ninne Zahara Silviani (ConCEPt - Conference on Community Engagement Project, 2022)
Waste management in Batam City is an important aspect that must be monitored carefully because it is closely related to environmental sanitation and order. For Batam city, regulations regarding waste management are regulated in Regional Regulation Number 11 of 2013 concerning Waste Management in Batam City. In this article, the author will explain how the implementation of this Regional Regulation in Batam City is related to the handling of illegal landfills (TPS) which of course causing a negative impact on the environment and also the appropriate penalty to countermeasures this problem. In this article, the method used by the author is the implementation method as for the stages, namely: The initial stage is preparation of PKM to agencies regarding the application for PKM permits and permission to conduct research related to the title chosen. The next stage will be observation and identification of the subject matter and carry out data collection to be analyzed at the Batam City Environmental Service. The author makes a project output design based on the practical workplace conditions. The last stage in this is the author processes the data that has been obtained and makes a PKM report. Then the author also designs the output which is the result of the practical work.